巫俊锋影片中再现的同志和家国认同 = Representation of homosexuality and national identity in Singapore : a study on Boo Junfeng’s films - 黄露霆 Wong, Lu Ting (2013)
同志的话题在九十年代以前还是一个禁忌话题，以致没有人敢讨论同志，同志们也只能生活在自己的小房间里。一直到了近年，新加坡同志的课题开始备受讨论，其中一个经常引起人们对于同志的讨论课题便是自2009年开始的粉红点活动。 身为粉红点的其中一位策划人以及短片导演的巫俊锋不仅仅为粉红点拍摄短片，也在粉红点开始前拍摄了一些同志为题材的短片。通过巫俊锋所拍摄的同志题材短片，他希望能够引发观众的一些思考，并且在观赏后能够摒除和消解一些对于同志的偏见和误解。 Homosexuality was a taboo in the nineties, so homosexuals can only live in their own closets. It was only until recently that homosexuality had become a topic of discussion in Singapore, one of which was the Pink Dot, which was started in 2009.